Evaluation of the Effect of Consciousness Energy Healing Treatment on the Physicochemical and Thermal Properties of Selenium - Nayak Gopal; Kumar Trivedi Mahendra; Branton Alice; Trivedi Dahryn; Jana Snehasis (Journal of New Developments in Chemistry, 2018)
Selenium is an essential micronutrient required for healthy metabolism, as well as prevention, and treatment of selenium deficiency diseases. The experiment aimed to evaluate the influence of the Trivedi Effect®-Consciousness Energy Healing Treatment on the physicochemical and thermal properties of selenium using modern analytical techniques. The selenium sample was divided into two parts, one part of the test sample was called the control sample, while the second part of the test sample received the Biofield Treatment remotely by a renowned Biofield Energy Healer, Gopal Nayak, and was called the treated sample. The particle size values were significantly decreased by 37.69% (d10), 14.36% (d50), 4.31% (d90), and 11.58% D(43), hence, the specific surface area was significantly increased by 33.64% in the treated sample compared to the control sample. The PXRD peak intensities and crystallite sizes were significantly altered ranging from 5.23% to 100% and 75% to 111.7%, respectively; whereas 7.81% significantly decreased the average crystallite size in the treated sample than the control sample. The latent heat of fusion of the treated sample was significantly increased by 12.37% compared with the control sample.The results suggested that the Trivedi Effect® might generate a new polymorphic form of selenium which would offer better solubility, bioavailability and be thermally more stable compared with the control sample. The Biofield Treated selenium would be more useful to design novel nutraceutical/pharmaceutical formulations and might offer an enhanced therapeutic response against cardiovascular disease, cancer, neuromuscular disorders, diabetes, stress, aging, male infertility, viral diseases, degenerative ailments, etc.
Keywords: Selenium